Currently unavailable: until 03/06/2016
Degree: Mathematics (Bachelors) - Exeter University
|Maths||13 Plus||£18 /hr|
Firstly we rearrange one of these equations so that we have y on one side of the equation on its own. Let's do this with the second equation.
So from 5x+y=14, we can minus 5x from both sides to get:
Then we can substitute this expression for y into our first equation that is 3x+2y=7
So we have 3x+2(14-5x)=7
Then we expand the bracket:
By simplifying this equation we get:
And simplifying further gives:
By dividing both sides by 7, we find that x=3.
We substitute this value for x into either of our original equations to find the value of y.
And therefore y=-1.
Finally we can check our solutions by substituting x=3 and y=-1 into the other original equation.
Therefore the solutions are x=3 and y=-1.see more